Chemical quality and regulatory compliance of drinking water in Iceland ... - Bartram, Jamie; Gardarsson, Sigurdur M.; Gunnarsdottir, Maria J.; Jonsson, Gunnar St. (The University of North Carolina at Chapel Hill University Libraries, 2016)
Assuring sufficient quality of drinking water is of great importance for public wellbeing and prosperity. Nations have developed regulatory system with the aim of providing drinking water of sufficient quality and to minimize the risk of contamination of the water supply in the first place. In this study the chemical quality of Icelandic drinking water was evaluated by systematically analyzing results from audit monitoring where 53 parameters were assessed for 345 samples from 79 aquifers, serving 74 water supply systems. Compliance to the Icelandic Drinking Water Regulation (IDWR) was evaluated with regard to parametric values, minimum requirement of sampling, and limit of detection. Water quality compliance was divided according to health-related chemicals and indicators, and analyzed according to size. Samples from few individual locations were benchmarked against natural background levels (NBLs) in order to identify potential pollution sources. The results show that drinking compliance was 99.97% in ...